Discovery of Heterocyclic Nonacetamide Synaptic Vesicle Protein 2A (SV2A) Ligands with Single‐Digit Nanomolar Potency: Opening Avenues towards the First SV2A Positron Emission Tomography (PET) Ligands. Issue 4 (20th January 2014) - Mercier, Joël; Archen, Laurence; Bollu, Véronique; Carré, Stéphane; Evrard, Yves; Jnoff, Eric; Kenda, Benoît; Lallemand, Bénédicte; Michel, Philippe; Montel, Florian; Moureau, Florence; Price, Nathalie; et al.
Abstract The role of the synaptic vesicle protein 2A (SV2A) protein, target of the antiepileptic drug levetiracetam, is still mostly unknown. Considering its potential to provide in vivo functional insights into the role of SV2A in epileptic patients, the development of an SV2A positron emission tomography (PET) tracer has been undertaken. Using a 3D pharmacophore model based on close analogues of levetiracetam, we report the rationale design of three heterocyclic non‐acetamide lead compounds, UCB‐A, UCB‐H and UCB‐J, the first single‐digit nanomolar SV2A ligands with suitable properties for development as PET tracers.